The Audiometric Findings among Curitiba and Metropolitan Area Students - Klas, Regina; Lacerda, Adriana (International Archives of Otorhinolaryngology, 2014)
Introduction Hearing loss can compromise the language, learning process, and socialization of students.Objective Study the audiometric findings among Curitiba and Metropolitan Area students.Methods Analysis of data collected at the hearing health service of Paraná State special education and inclusion department.Results The sample consisted of 646 students, children and teenagers of both genders (38.2% female and 61.8% male), with average age of 8.12 years (range 2 to 15); all were students of public or private schools of Curitiba and Metropolitan Area. The justifications to refer the students to audiometric evaluation were: otolaryngologists diagnosis (73.1%), school difficulties (39.6%), and midlevel hearing problems (32%). Audiometric results showed that 29.5% of the students had hearing loss. Conductive hearing losses showed the greatest occurrence among preschool students (right ear 38.6%, left ear 39.8%). The predominant hearing loss degree was mild (RE 20.5%, LE 19.3%) to slight (RE 17%, LE 19.3%), as was the horizontal configuration (RE 81.5%, LE 78.4%). A significant relationship (p = 0.0000) between hearing loss and poor school performance was noted.Conclusion Considering the available data, especially the high number of findings of conductive losses, it is necessary to highlight prevention and diagnosis of early hearing alteration. Nevertheless, Brazil, as an emerging country, has been pursuing improvement in health and life quality of all citizens.
Keywords: hearing; hearing loss; public health